High throughput screening for discovery of materials that control stem cell fate - Patel, Asha K.; Tibbitt, Mark; Celiz, Adam D.; Davies, Martyn C.; Langer, Robert; Denning, Chris; Alexander, Morgan R.; Anderson, Daniel G. (Elsevier, 2016)
Insights into the complex stem cell niche have identified the cell–material interface to be a potent regulator of stem cell fate via material properties such as chemistry, topography and stiffness. In light of this, materials scientists have the opportunity to develop bioactive materials for stem cell culture that elicit specific cellular responses. To accelerate materials discovery, high throughput screening platforms have been designed which can rapidly evaluate combinatorial material libraries in two and three-dimensional environments. In this review, we present screening platforms for the discovery of material properties that influence stem cell behavior.